Deciphering the domain specificity of C. difficile toxin neutralizing antibodies. Issue 29 (27th June 2019) - Cole, Leah E.; Li, Lu; Jetley, Utsav; Zhang, Jinrong; Pacheco, Kristl; Ma, Fuqin; Zhang, Jianxin; Mundle, Sophia; Yan, Yanhua; Barone, Lucianna; Rogers, Christopher; Beltraminelli, Nicola; et al.
Abstract: Clostridium difficile infection (CDI) is the principal cause of nosocomial diarrhea and pseudomembranous colitis associated with antibiotic therapy. The pathological effects of CDI are primarily attributed to toxins A (TcdA) and B (TcdB). Adequate toxin-specific antibody responses are associated with asymptomatic carriage, whereas insufficient humoral responses are associated with recurrent CDI. While the data supporting the importance of anti-toxin antibodies are substantial, clarity about the toxin domain specificity of these antibodies is more limited. To investigate this matter, combinations of human mAbs targeting multiple domains of TcdB were assessed using toxin neutralization assays. These data revealed that a combination of mAbs specific to all major toxin domains had improved neutralizing potency when compared to equivalent concentrations of a single mAb or a combination of mAbs against one or two domains. The function and toxin domain binding specificity of serum antibodies elicited by immunization of hamsters with a toxoid vaccine candidate was also assessed. Immunization with a toxoid vaccine candidate provoked toxin neutralizing antibodies specific to multiple domains of both TcdA and TcdB. When assessed in a toxin neutralization assay, polyclonal sera displayed greater activity against elevated concentrations of toxins than equivalent concentrations of individual mAbs. These data suggest a potential benefit of any antibody based therapeutic or prophylactic treatment that targets multiple toxin domains.